1999
DOI: 10.1152/jappl.1999.86.3.1048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of O2 supply-dependentV˙o 2 max in the exercise-trained human quadriceps

Abstract: Maximal O2 delivery and O2 uptake (VO2) per 100 g of active muscle mass are far greater during knee extensor (KE) than during cycle exercise: 73 and 60 ml. min-1. 100 g-1 (2.4 kg of muscle) (R. S. Richardson, D. R. Knight, D. C. Poole, S. S. Kurdak, M. C. Hogan, B. Grassi, and P. D. Wagner. Am. J. Physiol. 268 (Heart Circ. Physiol. 37): H1453-H1461, 1995) and 28 and 25 ml. min-1. 100 g-1 (7.5 kg of muscle) (D. R. Knight, W. Schaffartzik, H. J. Guy, R. Predilleto, M. C. Hogan, and P. D. Wagner. J. Appl. Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
178
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(210 citation statements)
references
References 31 publications
22
178
2
8
Order By: Relevance
“…Previous studies have found the 1-KE mass-specific O 2 uptake, measured by invasive methods, to range from 350 to 602 ml·kg -1 ·min -1 (Andersen & Saltin, 1985i;Rowell et al, 1986;Richardson et al, 1993a;Radegran et al, 1999a;Richardson et al, 1999a;Mourtzakis et al, 2004). The mass specific O 2 uptake found in the present study of 386 and 570 ml·kg -1 ·min -1 for controls and ET, closely agree with this range.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies have found the 1-KE mass-specific O 2 uptake, measured by invasive methods, to range from 350 to 602 ml·kg -1 ·min -1 (Andersen & Saltin, 1985i;Rowell et al, 1986;Richardson et al, 1993a;Radegran et al, 1999a;Richardson et al, 1999a;Mourtzakis et al, 2004). The mass specific O 2 uptake found in the present study of 386 and 570 ml·kg -1 ·min -1 for controls and ET, closely agree with this range.…”
Section: Discussionsupporting
confidence: 89%
“…The highest mass-specific bloodflow and VO 2 in humans is probably achieved during 1-KE (Andersen et al, 1985a;Richardson et al, 1995b). Due to overperfusion, and therefore a short capillary mean transit time of the blood cells, the muscles would probably not reach higher mass-specific VO 2 without increasing the arterial PO 2 (Richardson et al, 1995a;Richardson et al, 1999b;Richardson et al, 1993c). 1-KE exercise is therefore a widely accepted method of quantifying the muscular metabolic capacity in vivo in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is prior evidence in subjects performing small-muscle-mass submaximal exercise that suggests the effect of varying FI O 2 on O 2 delivery is dampened by an alteration in muscle blood flow (28). Specifically, it has been shown that across a range of submaximal work intensities muscle blood flow is elevated to compensate for the reduced arterial O 2 content in hypoxia and decreased in hyperoxia, thus either partially or totally compensating, in terms of O 2 delivery, for changes in arterial O 2 content (20,24 In our laboratory's previous study (7), the increase in the PCr recovery rate constant in hyperoxia and decrease in hypoxia for the physically active group is also suggestive of this scenario because the most significant effect of hyperoxia is to raise blood PO 2 because hemoglobin saturation is already close to its ceiling in normoxia (and muscle blood flow tends to fall in hyperoxia). Hence, it is suggested that in hyperoxia the driving gradient from blood to muscle was enhanced, resulting in an elevated intracellular PO 2 , facilitating increased oxidative metabolism, and ultimately increased PCr recovery rate constants.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the Larginine NOS pathway becomes dysfunctional with low O2 tensions and pH [33]. Such cellular conditions are likely to be especially prevalent during exercise in a hypoxic environment [8,34], such as experienced on ascent to terrestrial altitude. This suggests that nitrate supplementation may be more likely to enhance NO generation and therefore improve performance in hypoxia relative to normoxia.…”
Section: Introductionmentioning
confidence: 99%